ChemInform Abstract: Carbon Coated Li4Ti5O12 Nanorods as Superior Anode Material for High Rate Lithium Ion Batteries. Issue 32 (18th July 2013) - Luo, Hongjun; Shen, Laifa; Rui, Kun; Li, Hongsen; Zhang, Xiaogang
Abstract Carbon coated Li4Ti5O12 nanorods for high‐rate Li ion batteries are prepared by mixing anatase‐phase TiO2 with glucose and KOH (stirring and sonication, 1 h) followed by hydrothermal treatment (autoclave, 180 °C, 1 d) and dispersing the obtained nanorods in LiOH solution (autoclave, 150 °C, 6 h) before calcination of the obtained precursor (600 °C, 2 h).